The Impact of Implementing Enterprise Resource Planning on Performance and Workforce Needs at Agricultural Technology Companies in Jakarta - Ulfa, Riris Chanifatul; Girindra Mega Paksi (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
The economic industry has experienced development characterized by the industrial revolution. Currently, the world is facing the fourth industrial revolution marked by artificial intelligence, genetic engineering, and digital revolution. One form of digital transformation in companies is through the implementation of ERP. This system has a positive impact on company productivity, but also raises concerns with arguments that ERP systems could lead to job loss due to automation by companies. The aim of this research is to understand the potential of ERP in creating job opportunities and to identify challenges faced by the workforce as a result of ERP implementation. The research adopts a qualitative approach using interview and observation techniques.